Kejadian Anemia Kehamilan Dengan Perdarahan Postpartum - Sulpat, Emuliana; Kusumaningrum, Andri Tri; Harianto, Susilo; Mardhika, Amelia; Fadliyah, Lailatul; Pangestu , Anestasia (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Death of pregnant women due to bleeding is the main cause in Lamongan. The biggest cause is postpartum hemorrhage due to nutritional deficiencies, especially anemia. Anemia is one of the four main nutritional problems in Indonesia which has a fairly high prevalence and is often caused by nutritional deficiencies, especially iron. This study aims to determine the relationship between anemia in pregnancy and the incidence of postpartum hemorrhage. Methods: Design a case-control study with a retrospective observational approach, collecting data on maternal medical records in January-December 2021 in Bulutigo Laren-Lamongan Village, using a Simple Random Sampling technique with a sample size of 146 mothers who were divided into case groups and control groups. The dependent variable is anemia of pregnancy and the independent variable is postpartum hemorrhage. The research instrument used a check list to assess the incidence of anemia and an observation sheet to assess the incidence of postpartum hemorrhage. Data were analyzed by Chi Square test with ️ = 0.05. Results: The results of statistical tests showed that there was a significant relationship between anemia and the incidence of postpartum hemorrhage. The combined odds ratio (OR) showed that the effect of anemic pregnant women on postpartum hemorrhage was 45.7 times higher than that of non-anemic mothers (95% CI: 16.05-117.94; p<0.000). Conclusion: Pregnant women with anemia are 45.7 times more likely to experience postpartum hemorrhage than pregnant women who do not experience anemia. Anemia of pregnancy can be detected by regular antenatalcare (ANC) examinations